TUBULARIZED INCISED PLATE URETHROPLASTY FOR ONE-STAGE HYPOSPADIA REPAIR IN CHILDREN AT HASAN SADIKIN HOSPITAL BANDUNG - Oetama, Harris; Siregar, Safendra (Indonesian Journal of Urology, 2017)
Objective: To determine the outcome of tubularized incised-plate (TIP) urethroplasty for  one stage hypospadia repair in children. Material & methods: A 7-year retrospective experience at Hasan General Sadikin Hospital Bandung on the outcome of tubularized incised plate for one-stage hypospadias repair in children during 2009-2015. Results: A total of 102 children was undergone one stage hypospadias repair with TIP urethroplasty. The mean age was 6.97 years old. As much as 65 (63.72%) children had distal, and 37 (36.28%) children had proximal hypospadia. The mean length of surgery was 112.56 minutes. Post operative complications was rarely found, consisting of 5 (6.32%) children had urethrocutaneus fistula formation and 11 (13.9%) children had haematoma. 4 (10.81%) children with proximal hypospdia and 1 (1.53%) children with distal hypospadia had urethrocutaneus fistula formation. 4 (6.15%) children with distal hypospadia and 7 (18.91%) children with proximal hypospadia had haematoma. Conclusion: Tubularized incised-plate (TIP) urethroplasty for one stage hypospadia repair in children was highly effective with rare complications comparable with recently published study.